PROJECT-BASED LEARNING WITH POWTOON VIDEO: ENHANCE CRITICAL THINKING SKILLS IN CLASS V IPAS LEARNING - Fatimah, Anissa Khusnul; Rusnilawati, Rusnilawati (Jurnal Ilmiah Didaktika, 2025)
The background of this study stems from the observation that teaching methods, such as problem-based learning using PowerPoint, tend to be less engaging and fail to optimally develop students’ critical thinking abilities. This study aims to analyze the effectiveness of applying the Project Based Learning model supported by Powtoon interactive video media on students' critical thinking skills on water cycle material in elementary schools. The method used was a quasi-experiment with a Non Equivalent Control Group design, involving two classes of 25 students each. The research instrument consisted of pre-test and post-test questions that had been tested for validity and reliability. The results showed that the application of the Project Based Learning model supported by Powtoon significantly improved students' critical thinking, especially in interpretation, analysis, evaluation, inference, explanation, information relate to the water cycle. In the results of Cosen's D analysis, the project-based learning model with powtoon video media has a very significant increase compared to the problem-based model with PPT media on students' critical thinking skills, this shows an effect size of 1.182 which means a very large influence.